Cerebral blood flow and cerebrovascular reactivity in Parkinson’s disease: relationship with severity of motor symptoms - Laura Pelizzari; Maria Marcella Laganà; Federica Rossetto; Niels Bergsland; Giuseppe Baselli; Mario Clerici; Raffaello Nemni; Mario Meloni; Francesca Baglio (Veins and Lymphatics, 2019)
Not available